ANALYSIS OF STRENGTHENING CUSTOMER LOYALTY IN DEPOSIT PRODUCTS AT BMT-UGT SIDOGIRI PAMEKASAN BRANCH - Sholehuddin, Moh; Ashari, Azis (Ngejha, 2023)
The main focus of this study is to evaluate the factors that affect customer loyalty and identify effective strategies for increasing customer satisfaction and attachment to deposit products. The qualitative research approach was used with a case study method at BMT-UGT Sidogiri Pamekasan Branch. Data was collected through in-depth interviews with customers, satisfaction surveys, and document analysis related to deposit management policies and practices. Data analysis is carried out descriptively to identify the main factors that affect customer loyalty, such as service quality, product benefits, and effective communication. The results show that several factors contribute significantly to strengthening customer loyalty, including satisfactory service, loyalty programs, and transparency in product information. In addition, a good communication strategy between BMT-UGT Sidogiri and customers has also been proven to increase satisfaction and loyalty. However, there are challenges such as the need for improved product features and responsiveness to customer feedback. This research provides insight into how BMT-UGT Sidogiri Pamekasan Branch can strengthen customer loyalty to deposit products through an integrated strategy that focuses on customer satisfaction. The recommendations provided are expected to help financial institutions in increasing customer engagement and achieving long-term success.